Pewarisan Anak Di Luar Nikah Dalam Perspektif Mazhab Syafi’i Dan Putusan Mahkamah Konstitusi Nomor 46/Puu-Viii/2010 - Suroaji, Ahmad; Hudi, Hudi; Munasir, Munasir (Isti`dal : Jurnal Studi Hukum Islam, 2024)
This research was motivated by the large number of children born outside of legal marriage or adultery. According to the Syafi'i School, children born out of wedlock cannot inherit from each other because the status of the father and the child's lineage has been absolutely severed, and the child only inherits from the mother and the mother's relatives. Meanwhile, in the Constitutional Court decision Number 46/PUU-VIII/2010 Children born out of wedlock only have a civil relationship with their mother and relatives of their mother and a man as their father who can be proven based on science and technology or other evidence according to the law to have a blood relationship, including a civil relationship with their father's family. The aim of this research is to find out the inheritance rights and position of illegitimate children from the perspective of the Syafi'i School and the perspective of the Constitutional Court. The method in this research uses qualitative research through literature study. The data used is primary and secondary data, this type of research is a descriptive analytical literature study, namely research that includes the process of collecting data, compiling and explaining the data and is related to the inheritance of children outside of marriage from the perspective of the Syafi'i School and the perspective of the Constitutional Court. Number 46/PUU-VIII/2010.